to find the derivative of F(x) you use the Power Rule which is d/dx (x^n) = nx^(n-1) and the Constant Rule which is d/dx (c) = 0
d/dx just means to take the derivative in terms of x, d/dx = F' = F'(x)
Power Rule: d/dx (x^n) = nx^(n-1)
Constant Rule: d/dx (c) = 0
(there are more derivative rules)
F(x) = 3x -5
d/dx F(x) = d/dx (3x-5)
F'(x) = 3x^(1-1) + 0
*(5 becomes 0 because of the Constant Rule and 3x becomes 3 because of the Power Rule)
F'(x) = 3
now we are supposed to plug in x = -3/4 into the derivative to get a y-value... but you can't because it's just a constant...
(Note: d/dx "means taking the derivative with respect to x" which means I want the derivative to contain x-variables. You might see dx/dy or d/dy which means to "take the derivative with respect to y", taking the derivative so that there are only y-variables...
For example, there might be an equation that looks like this:
V = 2x + x^2 and they ask you to find d/dx so you just find the derivative and since all the variables are x you are good. Now, if they want you to find d/dy then they want to find the derivative and they want the all the x-variables to be y-variables. You won't have to worry about that later when you learn the Chain Rule.)